PERANAN DINAS LINGKUNGAN HIDUP DALAM PENGAWASAN PENERAPAN AKUNTANSI LINGKUNGAN PADA ENTITAS BISNIS DI KABUPATEN PAMEKASAN - Evi Malia (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
The purpose of this study is to determine the role of DLH in overseeing business entities, especially companies that in their business activities produce waste. The method used in this study is a qualitative method. The results obtained are the duties of the Department of the Environment are 1) only overseeing business entities that already have environmental permits. 2) Supervision of the application of environmental accounting in business entities in Pamekasan Regency is in line with what is mandated by Law No. 32 of 2009 article 74 paragraph 1 as outlined in Pamekasan Regency Regulation No. 3/2013, environmental supervisors / officials have the authority to monitor businesses and / or activities that have the potential to pollute / damage the environment, request information from the party responsible for activities, make copy of documents / make notes, enter certain places suspected of causing environmental pollution / damage, take samples, examine equipment / installations and / or means of transportation, request information from parties related to the object of supervision. Keywords: Business Entity, Environmental Accoounting, Environmental Agency, Supervision